Diagnosis, treatment, and follow-up of borderline ovarian tumors - Fischerova, Daniela; Zikan, Michal; Dundr, Pavel; Cibula, David (The oncologist, 2012)
Borderline ovarian tumors represent a heterogeneous group of noninvasive tumors of uncertain malignant potential with characteristic histology. They occur in younger women, are present at an early stage, and have a favorable prognosis, but symptomatic recurrence and death may be found as long as 20 years after therapy in some patients. The molecular changes in borderline ovarian tumors indicate linkage of this disease to type I ovarian tumors (low-grade ovarian carcinomas). The pathological stage of disease and subclassification of extraovarian disease into invasive and noninvasive implants, together with the presence of postoperative macroscopic residual disease, appear to be the major predictor of recurrence and survival. However, it should be emphasized that the most important negative prognostic factor for recurrence is just the use of conservative surgery, but without any impact on patient survival because most recurrent diseases are of the borderline type-easily curable and with an excellent prognosis. Borderline tumors are difficult masses to correctly preoperatively diagnose using imaging methods because their macroscopic features may overlap with invasive and benign ovarian tumors. Over the past several decades, surgical therapy has shifted from a radical approach to more conservative treatment; however, oncologic safety must always be balanced. Follow-up is essential using routine ultrasound imaging, with special attention paid to the remaining ovary in conservatively treated patients. Current literature on this topic leads to a number of controversies that will be discussed thoroughly in this article, with the aim to provide recommendations for the clinical management of these patients.
Keywords: multicentrické studie jako téma; Prognosis; Multicenter Studies as Topic; laparotomie; Infertility; Laparoscopy; Neoplasm Recurrence, Local; nádory vaječníků; lokální recidiva nádoru; Chemoradiotherapy, Adjuvant; adjuvantní chemoradioterapie; ženské pohlaví; prognóza; Humans; infertilita; rizikové faktory; Laparotomy; Female; Ovarian Neoplasms; laparoskopie; Risk Factors; lidé